EFFECTIVE ANESTHESIA FOR ONCOGYNECOLOGICAL SURGERIES IN FEMALE PATIENTS WITH CONCURRENT OBESITY - M. A. Аnisimov; E. S. Gorobets; I. A. Yakushina (Вестник анестезиологии и реаниматологии)
The basic pathophysiologic characteristics, technical difficulties and handling methods thereof, including among others the difficult respiratory passages, the characteristics of ventilation and oxygenation, circulatory dynamics, dependence on the patient’s position on the operation table are described by the example of 60 gynecological cancer patients with concurrent obesity. It is shown that as of today the multimodal combined anesthesia based on the tricomponent epidural analgesia in combination with sevoflurane and apparently desflurane appears to be the best choice of anesthetic protection during traumatizing surgical treatment for the cancer patients with the associated obesity. The focus is made on advisability of hemodynamic monitoring of these patients.